AB0671 Cardiovascular risk in systemic lupus erythematosus: Do renal risk factors play a part?. (23rd January 2014) - Atukorala, I.; Weeratunga, P.; Rathnamalala, N.; Kalubowila, J.; Ranasinghe, H.; Lanerolle, R.
Abstract : Background: Systemic lupus erythematosus (SLE) is associated with a high risk of cardiovascular disease (CVD). In addition to traditional risk factors, SLE disease related factors such as renal dysfunction are postulated to confer an increased CVD risk (1). Objectives: To correlate conventional CVD risk factors and lupus nephritis (LN) related risk factors in a cohort of LN patients using carotid intimal-media thickenss (CIMT) as a surrogate measure of CVD risk. Methods: Consecutive patients (n=40, of which n=38 were female) were recruited from the university research clinic, National Hospital Sri Lanka. The patients were evaluated for conventional CVD risk factors, renal parameters and extent of organ involvement. Current disease activity and damage were assessed by the BILAG score and SLICC/ACR damage index respectively. CIMT was assessed by B Mode grey scale ultasonography. Results: The mean age was 31 years (SD=8.87) with the average age at SLE diagnosis being 25 years (SD=6.7). Of these patients, 25% had neuropsychiatric manifestations, 87.5% had muco-cutaneous involvement, 20% had serositis, 47.5% had haematological involvement and 90% had arthritis. Previous acute coronary syndromes (7.5%), stable angina (5%), cerebrovascular accidents (7.5%), transient ischaemic attacks (2.5%), lower limb claudication(5%) and digital gangrene(5%) were documented. There were no current or ex-smokers. 72.5% had hypertension, 32.5% had dyslipidemias and 25% had diabetes. 40% were obese and 20% overweight (Asian cutoffs). 30% had elevated CRP. The LN patients were in Class I- 2.5%, II-12.5%, III-20%, IV-60%, V-5%. Nephrotic range proteinuria was present in 32% and chronic kidney disease (CKD) was present in 52% of patients (Stage 1 – 35%, Stage 2 – 43%, Stage 3 – 24%). CIMT was considered increased if more than the 75th percentile based on cutoffs from the "Carotid Atherosclerosis Progression Study". Increased CIMT (57.5%) and atherosclerotic plaques (15 36%) indicate a high CVD risk in this cohort. Diabetes (p=0.016), hypertension (p=0.002), dyslipdemia (p=0.002) and obesity (p=0.048) independently correlated with increased CIMT. Increased CIMT and plaques were not associated with high CRP or high current disease activity. A higher CIMT was observed with a significantly high cardiovascular (p=0.018) and peripheral vascular index (p=0.016) but not withproteinuria >3.5g/24h or estimated GFR<50% on the SLICC/ACR. Previous coronary disease (p=0.043) and atherosclerotic plaques (p=0.038) were significantly associated with nephrotic syndrome in univariate analysis but not with multivariate logistic regression which included conventional CVD risk factors. Conclusions: This LN cohort had varied organ involvement and a high prevalence of conventional CVD risk factors. Nephrotic range proteinuria and CKD did not confer an independently increased risk of CVD in cohort. The increased CVD risk prevalent was attributed to increased prevalence of conventional risk factors. References: Sazliyana S et al. Implications of immunosuppressive agents in cardiovascular risks and carotid intima media thickness among lupus nephritis patients. Lupus 2011; 20 (12): 1260-66. Disclosure of Interest: None Declared